Emulsions stabilized by chitosan/lithium dodecyl sulfate complexes - Thammasit Vongsetskul" (Science Faculty of Chiang Mai University, 2019)
The role of chitosan (CS), a biocompatible natural polymer, mixed with lithium dodecyl sulfate (LiDS), an anionic surfactant used as the emulsion stabilizer in cold conditions was investigated. The effects of LiDS concentration, CS concentration, and CS lengths on the stability of CS/LiDS complex-stabilized emulsions were studied using the ζ-potential, droplet size, and creaming stability measurements. The results revealed that the CS/LiDS complexes significantly improved the emulsion stability. The CS with 45 kiloDalton (kDa) could enhance the emulsion stability better than that of 100 kDa. The complex containing 1 mM LiDS and 1 g/L CS with 45 kDa were the optimal concentrations.